Sonographic findings of immunoglobulin G4-related sialadenitis and differences from Sjögren's syndrome. (4th March 2022) - Liu, Y; Wang, Z; Ren, L; Zeng, Q; Wang, Z; Bian, W; Zhang, Y; Fu, J; Chen, D; Yu, G; Zhang, S; Li, Z
Abstract : Objective: To evaluate ultrasonic features of the major salivary glands in patients with immunoglobulin G4 -related sialadenitis (IgG4 -RS) and to explore the differences between IgG4 -RS and Sjögren's syndrome (SS). Method: We conducted the study in 150 patients with IgG4 -RS and 100 patients with SS. Ultrasonographic variables of the static images of major salivary glands were analysed. An experienced radiologist scored the confidence rating regarding the presence of the characteristic imaging findings using a five-grade rating system. Ultrasonography scores between IgG4 -RS and SS were compared. Results: The major salivary glands were significantly larger in patients with IgG4 -RS than in the SS group. The main features of ultrasonography of the salivary glands in IgG4 -RS were various hypoechoic lesions and increased colour Doppler signalling. In contrast, the major salivary glands in SS exhibited hyperechoic lines and/or spots and obscuration of the gland configuration. The scores of the summarized sonographic characteristics also showed statistically significant differences between the IgG4 -RS and SS groups. Conclusion: This study revealed different ultrasonic features of the major salivary glands in patients with IgG4 -RS and SS. The scored sonographic features were helpful in differentiating IgG4 -RS from SS. Consequently, we suggest that ultrasonography of major salivary glands could be a useful imaging procedure in the evaluation of patients suspected of having IgG4 -RS.